Identification of a Novel Adhesion Molecule Involved in the Virulence of Legionella pneumophila - Chang, Bin (American Society for Microbiology, 2005)
Legionella pneumophila is an intracellular bacterium, and its successful parasitism in host cells involves two reciprocal phases: transmission and intracellular replication. In this study, we sought genes that are involved in virulence by screening a genomic DNA library of an L. pneumophila strain, 80-045, with convalescent-phase sera of Legionnaires' disease patients. Three antigens that reacted exclusively with the convalescent-phase sera were isolated. One of them, which shared homology with an integrin analogue of Saccharomyces cerevisiae, was named L. pneumophila adhesion molecule homologous with integrin analogue of S. cerevisiae (LaiA). The laiA gene product was involved in L. pneumophila adhesion to and invasion of the human lung alveolar epithelial cell line A549 during in vitro coculture. However, its presence did not affect multiplication of L. pneumophila within a U937 human macrophage cell line. Furthermore, after intranasal infection of A/J mice, the laiA mutant was eliminated from lungs and caused reduced mortality compared to the wild isolate. Thus, we conclude that the laiA gene encodes a virulence factor that is involved in transmission of L. pneumophila 80-045 and may play a role in Legionnaires' disease in humans.